Hexapodibius christenberryae, a new species of tardigrade from North America (Eutardigrada, Calohypsibiidae) - Pilato, Giovanni; Binda, Maria Grazia (Zootaxa, 2003)
A new species of Hexapodibius is described: Hexapodibius christenberryae, from North America. It is the only known species of Hexapodibius having only two macroplacoids. The other five species of the genus known to date have three macroplacoids.